2007
DOI: 10.1177/104063870701900109
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of the Prevalence and Features of Postweaning Multisystemic Wasting Syndrome in Japan

Abstract: Abstract. To investigate the prevalence and features of postweaning multisystemic wasting syndrome (PMWS) in Japan, an epidemiological study was conducted in 692 weaned pigs with various clinical signs, commonly including wasting or weight loss, collected from 129 swine farms between 2000 and 2003. The presence of PMWS was diagnosed by the detection of characteristic histological lesions and moderate to large amounts of porcine circovirus type 2 (PCV2) antigen within the lesions in multiple lymphoid tissues. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
(53 reference statements)
0
20
0
2
Order By: Relevance
“…It causes not only the progressive loss of body conditions, mortality and congenital tremor A2 (CT-AII) in weaned piglets ), but also abortion in pregnant sows (O'Connor et al 2001), porcine respiratory disease syndrome (PRDS) and porcine dermatitis nephritis syndrome (PDNS) in adult pigs (Johnstone and Lawton 2008;Phaneuf et al 2007). These diseases severely affect the pig industry, and cause huge economic losses worldwide Liu et al 2002;Gresham et al 2000;Grau-Roma et al 2009;Kawashima et al 2007;Elbers et al 2000). With the aim to study the disease caused by PCV-2, developing animal models for PCV-2 infection has been studied since the pathogenicity of PCV-2 was demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…It causes not only the progressive loss of body conditions, mortality and congenital tremor A2 (CT-AII) in weaned piglets ), but also abortion in pregnant sows (O'Connor et al 2001), porcine respiratory disease syndrome (PRDS) and porcine dermatitis nephritis syndrome (PDNS) in adult pigs (Johnstone and Lawton 2008;Phaneuf et al 2007). These diseases severely affect the pig industry, and cause huge economic losses worldwide Liu et al 2002;Gresham et al 2000;Grau-Roma et al 2009;Kawashima et al 2007;Elbers et al 2000). With the aim to study the disease caused by PCV-2, developing animal models for PCV-2 infection has been studied since the pathogenicity of PCV-2 was demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…PCV2 DNA was detected in 86.2-100% of farms between 2000 and 2003 [9]. These studies indicate a high prevalence of PCV2 infection on pig farms in Japan.…”
mentioning
confidence: 71%
“…As a result, it appears that immunosuppressive factors at the beginning of the nursery period may contribute to infection with M. hyorhinis. Several studies have shown the association of M. hyorhinis with other infectious agents and immunosuppressive factors, such as stress (Kinne et al 1991, Kawashima et al 1996, Kawashima et al 2007, Kixmoller et al 2008, which enables M. hyorhinis to colonize and propagate in these individuals. Reinforcing the hypothesis that M. hyorhinis could be considered a secondary agent of pneumonic lesions, experimental studies involving this pathogen rarely showed areas of pneumonia, and when pneumonic lesions were present they were mild and affected a small percentage of the inoculated animals (Poland et al 1971, Lin et al 2006).…”
Section: Discussionmentioning
confidence: 99%